The Holocaust : a new history - Rees, Laurence, 1957- 1957- (Viking, 2017)
This landmark work answers two of the most fundamental questions in history - how, and why, did the Holocaust happen? Laurence Rees has spent twenty-five years meeting survivors and perpetrators of the Holocaust. Now, in his magnum opus, he combines their enthralling eyewitness testimony, a large amount of which has never been published before, with the latest academic research to create the first accessible and authoritative account of the Holocaust in more than three decades. This is a new history of the Holocaust in three ways. First, and most importantly, Rees has created a gripping narrative that that contains a large amount of testimony that has never been published before. Second, he places this powerful interview material in the context of an examination of the decision making process of the Nazi state, and in the process reveals the series of escalations that cumulatively created the horror. Third, Rees covers all those across Europe who participated in the deaths, and he argues that whilst hatred of the Jews was always at the epicentre of Nazi thinking, what happened cannot be fully understood without considering the murder of the Jews alongside plans to kill millions of non-Jews, including homosexuals, 'Gypsies' and the disabled. Through a chronological, intensely readable narrative, featuring enthralling eyewitness testimony and the latest academic research, this is a compelling new account of the worst crime in history